2022
DOI: 10.1136/bmjgast-2022-000947
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and symptoms in women aged 20–49 years and relation to upper gastrointestinal and colon cancers

Abstract: ObjectiveIron deficiency anaemia (IDA) in women aged 20–49 years may be caused by menses or gastrointestinal cancer. Data are sparse on the yield of endoscopy/colonoscopy in this population. Our aim was to determine the association of IDA and symptoms with cancers.DesignRetrospective cohort study within Kaiser Permanente Northern California. Participants were women aged 20–49 years tested for iron stores and anaemia during 1998, 2004 and 2010 and followed for 5 years for outcomes of oesophageal, gastric and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In their study, men and postmenopausal women had a 31 times greater risk of malignancy in the presence of IDA and 5 times greater risk with NAID. This is reflected in multiple other studies that have identified that GI malignancies in women of menstruating age are rare, with no change in risk in the presence of iron deficiency 7,15 . We were unable to complete a subgroup analysis for premenopausal and postmenopausal women with IDA or NAID due to missing data.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In their study, men and postmenopausal women had a 31 times greater risk of malignancy in the presence of IDA and 5 times greater risk with NAID. This is reflected in multiple other studies that have identified that GI malignancies in women of menstruating age are rare, with no change in risk in the presence of iron deficiency 7,15 . We were unable to complete a subgroup analysis for premenopausal and postmenopausal women with IDA or NAID due to missing data.…”
Section: Discussionmentioning
confidence: 94%
“…This is reflected in multiple other studies that have identified that GI malignancies in women of menstruating age are rare, with no change in risk in the presence of iron deficiency. 7,15 We were unable to complete a subgroup analysis for premenopausal and postmenopausal women with IDA or NAID due to missing data. But in our iron-deficient cohort, male gender conferred a three times greater risk of malignancy overall.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that upper GI cancer and CRC overall are rare in women of childbearing age and are not affected by the presence or absence of IDA. However, when symptoms rather than IDA were used as an indication for endoscopy, they found the same number of cancers with fewer procedures (Szpakowski and Tucker 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…found out IDA anemia is common in women aged 20–49 years due to excessive menses and gastrointestinal cancers. [ 12 ] A high prevalence has been documented in preschool children and women in the reproductive age group in Africa and Southeast Asia. [ 13 ] The etiology of IDA is multifactorial, and the causes include nutritional deficiencies, chronic and acute infections, blood dyscrasias, obesity, and parasitic infestations.…”
Section: Discussionmentioning
confidence: 99%